2015
DOI: 10.2174/1566524015666150731100012
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Expression Profile in Aqueous Humor and Sera of Patients with Acute Anterior Uveitis

Abstract: Cytokine expression pattern in the aqueous humor, in contrast to that in serum, may reflect intraocular immune reactions during active inflammation in patients with AAU. Both Th1 and Th17 are involved in immunopathogenesis of HLA-B27 associated and idiopathic AAU, but a different cytokine pattern was identified in these two clinical entities. A predominant Th17-driven immune response may play an important role in the immunopathogenesis of idiopathic AAU, while Th1 dominant immune response may be responsible fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(61 citation statements)
references
References 0 publications
5
54
0
2
Order By: Relevance
“…This observation is common to AqH studies, and advocates the use of AqH for studying these Cytokines in HIV-associated Eye Infections 77 diseases. 8,9,21,22 Individuals with CMVr had higher concentrations of GM-CSF, IL-1α, and IP-10 in AqH. A trend towards a T H 1 response cytokine was observed in both OIs, and not only in those with CMVr, as previously reported.…”
Section: Discussionsupporting
confidence: 80%
“…This observation is common to AqH studies, and advocates the use of AqH for studying these Cytokines in HIV-associated Eye Infections 77 diseases. 8,9,21,22 Individuals with CMVr had higher concentrations of GM-CSF, IL-1α, and IP-10 in AqH. A trend towards a T H 1 response cytokine was observed in both OIs, and not only in those with CMVr, as previously reported.…”
Section: Discussionsupporting
confidence: 80%
“…The high incidence of uveitis among JCA patients may increase the progression of myopia. Higher expression levels of the inflammatory cytokines IL-6 and TNF-α were found in the aqueous humor of uveitis patients (Chen et al, 2015). These increased levels of IL-6 and TNF-α in the eye support the progression of myopia.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that IL-18 participates in the pathogenesis of BD and its levels are correlated with the disease activity (Musabak et al, 2006). Our previous study has suggested a predominant Th17-driven immune response may play an important role in the immunopathogenesis of idiopathic AAU, while Th1 dominant immune responses may be responsible for the inflammation in HLA-B27 associated AAU (Chen et al, 2014). In the current study, significantly increased levels of IL-18 are observed in aqueous humor from patients with HLA-B27 associated AAU compared to that in idiopathic AAU, which further supports the hypothesis that Th1-type immune responses may be more relevant in HLA-B27 associated AAU compared to idiopathic AAU.…”
Section: Q2mentioning
confidence: 98%